Blood donation motivation in the United States and Russia: What keeps donors coming back?. (15th March 2022) - Sheldon, Kennon M.; Osin, Evgeny; Lapka, Samantha; Rasskazova, Elena; Titova, Liudmila; Khrushev, Sergei; Vybornykh, Dmitry; Gaponova, Tatiana
Abstract: What keeps regular blood donors coming back, despite the inconvenience and discomfort, thereby maintaining the community's blood supply? We approached 494 people waiting to give blood, 229 Americans and 265 Russians, with a survey that assessed their motivations to donate, their contextual emotions, and their future donation intentions. The Russian sample was older, and many were regulars at the donation centre. The U.S. sample was younger, attending a 3‐day college blood drive. Multigroup path analysis results showed that, as hypothesised, in both samples, autonomous donation motivations predicted contextual emotions and future donation intentions. Furthermore, contextual emotions partially mediated the motivation‐to‐future intentions effect. Small differences in results for the two samples, as well as differences in the two national systems for maintaining blood supplies, are discussed.